DAYA TETAS DAN LAMA MENETAS TELUR AYAM TOLAKI PADA MESIN TETAS DENGAN SUMBER PANAS YANG BERBEDA - Nafiu, La Ode (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2014)
This study aims to determine the hatchability and long of hatching of tolaki chicken eggs in incubator with different heat sources. Research carried out for 5 months in breeding cage Faculty of Animal science Halu Oleo University. Â Chicken Tolaki used consisted of 5 males and 15 females aged approximately 20 months. Mating chicken is done by IB. Parameters measured were: (1) fertility, embryo viability, hatchability, hatching weight and long hatch. The results showed: (1) the average fertility Tolaki chicken eggs in PL incubator is 58.57% and PLM incubator is 46.88%, but both the incubator statistically was not significantly different, (2) the average of DHE in PL incubator is 96.67% and PLM incubator is 89.58%, (3) the average hatchability in PL incubator is 45.61% and PLM incubator is 64.81%, (4) the average weight of hatching in PL incubator is 26.47 g, while the PLM incubator is 26.96 g, and (5) long the eggs hatch in PL incubator is 21,05 days and PLM is 21,09 days. Statistically, the use incubator with different heat source had no significant effect on all parameters were observed.Based on the discussion concluded that incubator with different heat source does not significantly affect on fertility, DHE, hatchability, hatching weight and length of hatching of Tolaki chicken eggs, but to improve the hatchability is recommended to use incubator with a combination electric and oil lamps heat sources. Key words: fertility, embryo viability, hatchability and length of hatching, and tolaki chicken.